9-(Methylsulfanyl)acridinium trifluoromethanesulfonate - Zadykowicz, Beata (International Union of Crystallography, 2009)
In the crystal structure of the title compound, C(14)H(12)NS(+)·CF(3)SO(3) (−), N—H⋯O hydrogen bonds link cations and anions into ion pairs. Inversely oriented ion pairs form stacks through multidirectional π–π interactions among the acridine units. The crystal structure features a network of C—H⋯O interactions among stacks and also long-range electrostatic interactions among ions. In the packing of the molecules, the acridine units are nearly parallel in stacks or inclined at an angle of 33.07 (2)° in the four adjacent stacks with which they interact via weak C—H⋯O interactions. The methylsulfanyl group is twisted through an angle of 60.53 (2)° with respect to the acridine ring.